Sero - Conversion After measles Immunization - Saxena D.K; Kantharia S.L; Mehta N.R (Wolters Kluwer Medknow Publications, 1989)
174 children of 9 to 23 months age from different localities of Surat city (Gujrat) were studied for sero-conversion by estimation of pre and post measles immunization H.I. antibody titres. 71 children and detectable H.I. antibody titres (16). Sero â€" conversion rate was 74.7 % in children having detectable H.I. antibodies. Increasing age, higher levels of H.I. antibody titres and prolonged interval between immunization and collection of post immunization blood sample had negative effects on sero â€" conversion. There was no effect of malnutrition and Socio- economic status on sero- conversion is discussed. The filter paper technique though simple and very suitable for field conditions, has a tendency to under report the sero â€" conversion after measles immunization.